pem, me, peng, budi Pengelolaan Sampah Rumah Tangga yang Inovatif Berbasis Partisipasi Aktif Masyarakat di Nagari Situjuah Banda Dalam - Mislaini Rahman; Nurwanita Ekasari Putri; Ely Vebriyanti (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2026)
Situjuah Banda Dalam Village is a village in Situjuah Limo Nagari District, 50 Kota Regency. It has a relatively high population density and community activities predominantly focused on agriculture, trade, and micro, small, and medium enterprises (MSMEs). These activities result in increasing household and business waste, but it has not yet been fully managed in an integrated manner. The current waste management system remains conventional and suboptimal. Most waste is managed independently by communities by burning, burying, or dumping it in open areas, including rivers, which contributes to environmental pollution. An effective Integrated Waste Processing Facility is not yet available.The objectives of this Community Service Program include: increasing public awareness and participation, reducing household and business waste generation, establishing a village-based waste management system, developing a waste-based circular economy, preserving the environment, and improving public health.The program's outcome is "Creative Recycling," a community empowerment-based activity that transforms plastic waste into useful, artistic, and even economically valuable products. The creative recycling program is implemented through three series of activities: plastic waste craft training, plastic waste bag making, and a plastic waste clothing fashion show. These activities are expected to make the community more skilled, productive, and motivated to manage waste in a more environmentally friendly manner.